1986
DOI: 10.1177/001872678603900502
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Groupthink Phenomenon

Abstract: This paper reports results of an empirical investigation of the groupthink theoreticalframework presented in Janis'second edition of Groupthink. Factor analysis was used to develop scales to measure the aspects of groupthink proposed by Janis (1982). Results supported some, but not all, of the symptoms and defects postulated by Janis. Next, a path analytic procedure was utilized to test the implied causal ordering of the Groupthink model (Janis, 1982, p. 244). This study provides limited support for the causal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 6 publications
5
66
0
Order By: Relevance
“…However, the results provide only partial validation of it (Esser , Herek et al. , Leana , Moorhead and Montanari ). In fact, researchers have criticized groupthink for several reasons.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…However, the results provide only partial validation of it (Esser , Herek et al. , Leana , Moorhead and Montanari ). In fact, researchers have criticized groupthink for several reasons.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…Instead, decisions are said to be made prematurely and without careful consideration of additional and alternative information. Despite the model's intuitive appeal and high degree of popularity, many have challenged its validity on the grounds that it lacks empirical support (e.g., Longley & Pruitt, 1980;Moorhead & Montanari, 1986). Although criticism of the model exists, some researchers have found at least partial support for the theoretical framework or variants of it (e.g., Henningsen, Henningsen, & Eden, 2006;Park, 2000).…”
Section: Groupthinkmentioning
confidence: 99%
“…Only under these situational circumstances, teams benefit from the inputs and unique ideas of team members to make more accurate team decisions (De Dreu et al, 2008;Jehn, 1995;Wang et al, 2014). We also found evidence to disprove the critique that associates directive leadership with poor team decision-making (Moorhead & Montanari, 1986;Tetlock et al, 1992). Our results show that that directive leadership appears to be a better predictor for team decision accuracy when dealing with routine situations.…”
Section: Theoretical Contributionssupporting
confidence: 56%
“…Furthermore, Srivastava et al (2006) showed that empowering leadership was positively related with knowledge sharing and team efficacy, which in turn were both positively related to team performance. Some scholars even accentuate that mainly directive leadership appears to be a root cause of team malfunctioning which leads to poor team decisions and thus poor team performance (Moorhead & Montanari, 1986;Tetlock et al, 1992). …”
Section: Leadership Style and Team Performancementioning
confidence: 99%